The Wright Brothers: The Story of the Strugggle to Build and fly the First Successful Aeroplane - Sproule, Anna (Exley Publishing Ltd, 1990)
The Wright Brothers mastery of flight changed the world. Orville Wright was in the air for only 12 seconds and covered only 120 feet. But those 12 seconds in the Mr made him the first person to fly a heavier-than-air machine, a full-sized vehicle that could be controlled by its pilot. On December 17, 1903 the beginnings of flight were mastered.
Keywords: Science & Technology; Biography & Autobiography; Juvenile Nonfiction